2021
DOI: 10.3390/ijgi10090584
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of Urban Land Expansion and Population Growth in Africa from 2001 to 2019: Evidence from Population Density Data

Abstract: Africa has been undergoing a rapid urbanization process, which is critical to the achievement of the 11th Sustainable Development Goal (SDG11). Using population density data from LandScan, we proposed a population density-based thresholding method to generate urban land and urban population data in Africa from 2001 to 2019, which were further applied to detect the spatiotemporal characteristics of Africa’s urbanization. The results showed that urban land and urban population have both grown rapidly in Africa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…In this paper, the proportion of new urban land in different periods, the annual increase in urban land and the annual urban growth rate were calculated to reveal spatiotemporal differences at regional and city levels. Theoretically, urban expansion includes not only the spread of urban land, but also the concentration of population, and there is a clear inconsistency between urban expansion and population expansion [61][62][63][64]. Many studies have found that population and economy play very important roles in urban land expansion [26,65,66]; therefore, it is of value to research the relationship among migration movements, economic growth, and urban land expansion.…”
Section: Current Limitations and The Way Forwardmentioning
confidence: 99%
“…In this paper, the proportion of new urban land in different periods, the annual increase in urban land and the annual urban growth rate were calculated to reveal spatiotemporal differences at regional and city levels. Theoretically, urban expansion includes not only the spread of urban land, but also the concentration of population, and there is a clear inconsistency between urban expansion and population expansion [61][62][63][64]. Many studies have found that population and economy play very important roles in urban land expansion [26,65,66]; therefore, it is of value to research the relationship among migration movements, economic growth, and urban land expansion.…”
Section: Current Limitations and The Way Forwardmentioning
confidence: 99%
“…To depict the rural settlement-population relationship in the process of rural development, the elasticity coefficient was used to partition the types of coupling development between rural settlement expansion and population growth [55,56]. The elasticity coefficient can be expressed as:…”
Section: Coupling Development Modelmentioning
confidence: 99%
“…Furthermore, a study conducted by [ 15 ] showed that Ethiopia is exhibiting a high annual rate of urbanization (5.4%). The Ethiopian urban population has more than doubled in the past 20 years, from 7.3 million in 1994 to 18 million in 2022 [ 14 ] with an annual growth rate of 6.82% between 2001 and 2019 [ 16 ], that is higher than the average in Sub-Saharan Africa (4.07%) [ 17 ]. However, the water supply and sanitation provision is not keeping up with the population growth.…”
Section: Introductionmentioning
confidence: 99%